2019
DOI: 10.3310/hta23080
|View full text |Cite
|
Sign up to set email alerts
|

Cabozantinib and vandetanib for unresectable locally advanced or metastatic medullary thyroid cancer: a systematic review and economic model

Abstract: BackgroundMedullary thyroid cancer (MTC) is a rare form of cancer that affects patients’ health-related quality of life (HRQoL) and survival. Cabozantinib (Cometriq®; Ipsen, Paris, France) and vandetanib (Caprelsa®; Sanofi Genzyme, Cambridge, MA, USA) are currently the treatment modality of choice for treating unresectable progressive and symptomatic MTC.Objectives(1) To evaluate the clinical effectiveness and safety of cabozantinib and vandetanib. (2) To estimate the incremental cost-effectiveness of cabozant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 67 publications
(227 reference statements)
0
23
0
Order By: Relevance
“…In the present study, we have attempted to give a view of the current status of TKI use in MTC, as reflected in the published literature. A recent, strict meta-analysis inquiring the effect of TKIs on PFS, combined with a network meta-analysis, included only the 2 phase III RCT trials [47], and showed a comparable efficacy.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, we have attempted to give a view of the current status of TKI use in MTC, as reflected in the published literature. A recent, strict meta-analysis inquiring the effect of TKIs on PFS, combined with a network meta-analysis, included only the 2 phase III RCT trials [47], and showed a comparable efficacy.…”
Section: Discussionmentioning
confidence: 99%
“…MTC is also a highly vascularized tumor with VEGF overexpression in tumor lesions 5 . Hence, multitarget TKIs (MKIs) blocking angiogenesis and RET are the classical medicines for the systemic therapy of MTC, such as vandetanib and cabozantinib [6][7][8][9][10][11] . The potency of other TKIs, including sorafenib 12 , pazopanib 13 , lenvatinib 14,15 , and sunitinib 16 , have also been explored.…”
Section: Introductionmentioning
confidence: 99%
“…However, liver staging in MTC remains challenging, as small metastases may remain 18 F-DOPA-negative. A timely and comprehensive liver staging is of major importance to evaluate potential treatment options with a growing oncological toolbox including local ablative treatment, surgical, or systemic therapy [1119]. Recent studies have shown that contrast-enhanced liver magnetic resonance imaging (MRI) is best suited for the detection of malignant liver lesions, particularly small metastases < 1.0 cm [2024].…”
Section: Introductionmentioning
confidence: 99%